Disentangling Forest Dynamics for Litter Biomass Production in a Biosphere Reserve in Central India - Thakur, Tarun Kumar; Eripogu, Kiran Kumar; Thakur, Anita; Kumar, Amit; Bakshi, Sanjeev; Swamy, S. L.; Bijalwan, Arvind; Kumar, Munesh (Frontiers in Environmental Science, 2022)
Investments in the energy sources are scaling up across India to improve energy security and further mitigate future climate change. The proper utilisation of the forest biomass and litterfall pattern plays an important role in sustainable management and utilization of resources. This study investigates the seasonal litterfall biomass pattern for consecutive 5 y (2015-2019) in four different vegetation types of central India (AABR) using the litter traps method on the forest floor. An ANOVA model was adopted to infer the effects of forest types, litter types, and seasonality on litterfall production. The estimated mean litterfall of the dry tropical forest in central India was recorded as 4.19±0.305 Mg/ha/y where teak plantations contribute higher values compared to other studied vegetation types. A positive correlation was observed between the litterfall and nutrient storage with soil-adjusted vegetation index and other vegetation indices. The findings of litterfall pattern and turnover rate of nutrients indicated that the vegetation types of AABR have huge potential for carbon sequestration and help to achieve the Conference of the Parties (COP-26) goal of reducing regional and/or global climate change.